Déficit de atención e hiperactividad y estrategias didácticas para trabajar en el aula en la Escuela de Educación Básica Particular “San Andrés”, periodo2023 - 2024 - Patiño Guaman, Sulay Anahi (2024)
The present curricular integration work had the objective of analyzing Attention Deficit Hyperactivity Disorder (ADHD) and didactic strategies to work on behavior in the classroom. Attention Deficit Hyperactivity Disorder (ADHD) represents a significant challenge in the educational setting, affecting both students' learning and teachers' ability to create an inclusive classroom environment. This study investigates instructional strategies to address ADHD at the Escuela de Básica Particular “San Andrés”, focusing on improving the academic performance and emotional well-being of students with ADHD is characterized by difficulties in attention, impulsivity and hyperactivity, which can hinder academic performance and classroom dynamics. Through interviews and observations, the study identified that students with ADHD often exhibit inattention, impulsivity, and disruptive behaviors during the school day. In this regard, specific teaching strategies were designed and implemented, such as the use of multisensory teaching methods, structuring the learning environment, and positive reinforcement. Data triangulation evidenced that students responded positively to strategies tailored to their individual needs, underscoring the importance of a personalized approach to teaching. With the implementation of the intervention plan, it can be concluded that the teachers improved significantly, they were able to maintain more attention than in the initial activities and they understood the orders they were given. Therefore, it is recommended to continue with the application of the plan as a model to build new activities, so that students with attention difficulties can be favored in this manner.